2011
DOI: 10.1103/physrevd.83.025015
|View full text |Cite
|
Sign up to set email alerts
|

Center vortex model for the infrared sector of SU(3) Yang-Mills theory: Topological susceptibility

Abstract: The topological susceptibility of the SU (3) random vortex world-surface ensemble, an effective model of infrared Yang-Mills dynamics, is investigated. The model is implemented by composing vortex world-surfaces of elementary squares on a hypercubic lattice, supplemented by an appropriate specification of vortex color structure on the world-surfaces. Topological charge is generated in this picture by writhe and self-intersection of the vortex world-surfaces. Systematic uncertainties in the evaluation of the to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 62 publications
0
28
0
Order By: Relevance
“…As far as we know, such a relation is not yet derived for SU(3) directly from the Yang-Mills theory, although some models for the SU(3) vortex (vortex-monopole net) [115,226,227] are proposed and studied, while for SU(2) some works give the numerical evidences for the existence of the vortex-monopole chains [80,225].…”
Section: The Role Of Magnetic Monopoles and Vortices For The Casimir mentioning
confidence: 99%
See 2 more Smart Citations
“…As far as we know, such a relation is not yet derived for SU(3) directly from the Yang-Mills theory, although some models for the SU(3) vortex (vortex-monopole net) [115,226,227] are proposed and studied, while for SU(2) some works give the numerical evidences for the existence of the vortex-monopole chains [80,225].…”
Section: The Role Of Magnetic Monopoles and Vortices For The Casimir mentioning
confidence: 99%
“…For the vortex surfaces for SU(N), N ≥ 3, may branch and the superimposed magnetic fluxes in general also modify the type of vortex flux, i.e., its direction in color space. See e.g., [115]. The (Z N ) vortex condensation theory for quark confinement put forward by 't Hooft [73], Mack [74], Cornwall [75] and by Nielsen, Olesen and Ambjorn [76] ("Copenhagen vacuum") is that the QCD vacuum is presumed to be filled with closed magnetic vortices, which carry magnetic flux in the center of the gauge group, and have the topology of tubes for D = 3 or surfaces for D = 4 of finite thickness.…”
Section: = 4 Vortexmentioning
confidence: 99%
See 1 more Smart Citation
“…Lattice simulations have shown that center vortices contribute to the topological charge via writhing, vortex intersections [33][34][35][36][37][38][39][40] and their color structure [41][42][43][44]. Vortices lead also to spontaneous χSB [45][46][47][48][49][50][51][52][53][54][55][56].…”
Section: Jhep09(2017)068mentioning
confidence: 99%
“…The vortex model can be applied to other infrared features of QCD not immediately related to confinement, such as the topological properties of gauge fields. In particular, it was shown how the topological susceptibility present in QCD can be calculated from center vortices [16][17][18][19][20][21][22][23] and vortices are also able to explain chiral symmetry breaking [24][25][26][27][28][29][30][31][32][33][34][35][36]. This way, the vortex model provides a unified picture for the infrared, low energy sector of QCD, explaining both confinement and the chiral and topological features of the strong interaction.…”
mentioning
confidence: 99%